2014
DOI: 10.1371/journal.pone.0093590
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Patterning of 1-D Collagenous Topography as an ECM Protein Fibril Platform for Image Cytometry

Abstract: Cellular behavior is strongly influenced by the architecture and pattern of its interfacing extracellular matrix (ECM). For an artificial culture system which could eventually benefit the translation of scientific findings into therapeutic development, the system should capture the key characteristics of a physiological microenvironment. At the same time, it should also enable standardized, high throughput data acquisition. Since an ECM is composed of different fibrous proteins, studying cellular interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Lee et al (28) found that stem cells patterned with rounded phenotypes differentiate into adipocyte‐like cells compared to cells with more spread phenotypes, which differentiate into neuron‐like cells. It has also been shown that ECM structure and the topography encountered by a cell can influence cell fate (2932).…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al (28) found that stem cells patterned with rounded phenotypes differentiate into adipocyte‐like cells compared to cells with more spread phenotypes, which differentiate into neuron‐like cells. It has also been shown that ECM structure and the topography encountered by a cell can influence cell fate (2932).…”
Section: Resultsmentioning
confidence: 99%
“…Various groups have developed methods to finely pattern electrospun nanofibers into organized structures. Fibers have been directed onto spinning mandrel collectors to create fiber spools [7], micropatterned via insulator-collector geometries to induce specific shapes [8] and positioned in precise locations by rapidly translating the collector with an X-Y stage [9][10][11][12]. The latter technique, sometimes termed direct-write electrospinning (DWES) is a relatively new additive manufacturing approach to electrospinning into highly organized confirmations.…”
Section: Introductionmentioning
confidence: 99%
“…First, the ability of EA.hy926 cells to deform the as-produced fibres were investigated; this was performed by comparing cell cultures maintained on three pure gelatin fibre configurations: fibres attached on glass, fibres suspended sparsely across a channel, and fibres forming a membrane with dense mesh. In the first test, the fibre pattern configuration was mostly fixed on the glass substrate like in our previous work [21]. Figure S4a shows that at day 1, cells form aligned patterns following those of the fibres, showing distinct orientations differing from the cells attached on the fibre-free space (i.e.…”
Section: Fibre and Membrane Mesh Remodelling Potentialmentioning
confidence: 68%
“…For the endothelial cell line (EA.hy926) culture, a protocol was adapted from [21] For the glomerular cell culture, conditionally immortalised human glomerular endothelial cell (GEnC) lines and podocytes cell lines were obtained and cultured according to [22,23]. A 3D ring-membrane device was immersed in DMEM for 1 hour before cell seeding, with the fibrous membrane facing the bottom of the 6-well plate.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation